Newbornscreening SMA - From Pilot Project to Nationwide Screening in Germany - Müller-Felber, Wolfgang; Blaschek, Astrid; Schwartz, Oliver; Gläser, Dieter; Nennstiel, Uta; Brockow, Inken; Wirth, Brunhilde; Burggraf, Siegfried; Röschinger, Wulf; Becker, Marc; Durner, Jürgen; Eggermann, Katja; et al. (Journal of Neuromuscular Diseases, 2023)
Now that targeted therapies for spinal muscular atrophy are available, attempts are being made worldwide to include screening for spinal muscular atrophy in general newborn screening. In Germany, after pilot projects from 2018-2021, it was included in the general newborn screening from October 2021. To ensure a smooth transition, criteria for follow-up were developed together with key stakeholders. At the beginning of the transition to nationwide screening, false positive findings were reported in 3 patients. After optimization of the screening method in the laboratories concerned, all findings have been subsequently confirmed. On average, the first presentation to a neuromuscular center occurred on day 12 of life, and in patients with 2 or 3 SMN2 copies, therapy started on day 26 of life. Compared with the pilot project, there was no significant delay in timing.
CRIS-Team Scopus Importer:2023-01-20
Keywords: 5q-SMA; newborn screening; SMA treatment; Spinal muscular atrophy